Analisis Sentimen Jasa Ekspedisi Pengiriman Barang Menggunakan Metode Naive Bayes - Matondang, Agnes Febrianti; Dur, Sajaratud; Cipta, Hendra (Universitas Cokroaminoto Palopo, 2024)
Based on the comment data that has been collected through data provided by the Nugraha Eka Courier route regarding serivce to customers, a sentiment analysis will e carried out to determine positive and negative comments. The collected data is divided to be used as training data and testing data for the classification process which is supported by the rapidminer application. The method used for clarification in this study is the Naïve Bayes method. This study aims to get the value of service accuracy based on comments given by the community. The results showed that the naïve bayes method was able to classify the comments that had been collected by getting an accuracy value for positive comments of 82,25% for negative comments getting an accuracy value of 17,75%. It is avident that the proposed method can be used to classify the services of the Nugraha Eka courier (JNE) line through the comments that have been collected.